Hannah Sharpe : Cartoon Detective - Book 1 - Tashjian, Janet; Tashjian, Jake, 1994- (New York : Little, Brown and Company, 2023)
Hannah Sharpe, an eleven-year-old cartoonist with Autism spectrum disorder, uses her curiosity, creativity, and amazing memory to investigate her familys newest Airbnb resident.
Ages 8-12.
Keywords: Cartoons and comics -- Juvenile fiction; Autism spectrum disorders -- Juvenile fiction; Lost and found possessions -- Juvenile fiction; Autism spectrum disorders -- Fiction; Lost and found possessions -- Fiction; JUVENILE FICTION / General; Detective and mystery fiction; Novels; Mystery fiction